Experimental and numerical evaluation of a folded plate girder system for short-span bridges – A case study. (15th April 2016) - Deng, Yaohua; Phares, Brent M.; Steffens, Owen W.
Highlights: Constructability and capacity of a folded plate girder system was evaluated experimentally. Rigorous non-linear FE models were established for comprehensive performance evaluation. Evolution of lateral load distribution was studied utilizing non-linear FE models. Abstract: Bridge owners and engineers focusing on bridge design, management and maintenance continue to search for more efficient ways to design, construct, and maintain their bridge inventory. Recently, a folded plate girder system has been promoted as a cost-effective alternative for the design and construction of bridge superstructures due to merits such as low cost and facilitation of accelerated bridge construction. The folded plate girder system has a structural shape strategically press-brake formed from a single sheet of plate steel and achieves composite action with a concrete deck utilizing shear studs in between. To further facilitate the development and adaptation of the system for bridge application, this paper presents a systematic performance evaluation of the folded plate girder system through experimental and numerical programs. To this end, a folded plated girder specimen was designed, fabricated, and tested to evaluate the constructability and capacity of the girder specimen. Finite Element (FE) Analysis was performed to understand the behavior of the girder specimen under different loading conditions. The predictions using traditional design calculations and FE analysis were compared with the test results. After the FE models were validated against the test data, a full bridge model was established to further investigate the behavior of the bridge under loading condition up to the ultimate load. It was found that the ultimate capacity of the bridge girders were much higher than the bridge demand and the bridge had good ductility until failure. The predictions using the design calculations based on the AASHTO LRFD Bridge Design Specifications were in reasonable agreement with the test results. The FE models showed better predictions since more sophisticated modeling techniques and material constitutive models were used. Results obtained from the sophisticated non-linear bridge model indicated that the girder distribution factors varied along with an increase of the truck loading and especially their change trend was gradually reversed after the yield of the girder steel. And according to the FE results, the distribution factor based on the AASHTO LRFD Bridge Design Specifications was sufficient for the design of the folded plate girder bridge investigated in this study.